2016
DOI: 10.5409/wjcp.v5.i1.89
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a pediatric bedside tool to predict time to death after withdrawal of life support

Abstract: In this external cohort, the DPT is clinically relevant in predicting time from withdrawal of life support to death. In our patients, the DPT is more useful in predicting death within 60 min of withdrawal of life support than within 30 min. Furthermore, our analysis suggests optimal cut-off scores. Additional calibration and modifications of this important tool could help guide the intensive care team and families considering DCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…In two external cohorts, the Dallas models did not achieve the predictive performance reported in the original study (16,17). Further, the optimal cutoff scores in the Das et al (17) validation differed considerably from the original study, which makes the tool impossible to use universally without further calibration and modification. The Winter et al (16) study assessed the Dallas model and also reported lower performance metrics than the original study.…”
Section: Limitationsmentioning
confidence: 81%
See 1 more Smart Citation
“…In two external cohorts, the Dallas models did not achieve the predictive performance reported in the original study (16,17). Further, the optimal cutoff scores in the Das et al (17) validation differed considerably from the original study, which makes the tool impossible to use universally without further calibration and modification. The Winter et al (16) study assessed the Dallas model and also reported lower performance metrics than the original study.…”
Section: Limitationsmentioning
confidence: 81%
“…In the Das et al (17) validation study of the Dallas models, sensitivity and specificity were lower than that reported by Shore et al (24). The authors identified that the Dallas 30-minute tool had the best performance at a score of greater than or equal to 3 (sensitivity, 0.76 and specificity, 0.52); the Dallas 60-minute tool had the best performance at a score of greater than or equal to 9 (sensitivity, 0.75 and specificity.…”
Section: Model Assessmentmentioning
confidence: 99%
“…The maximum functional warm recommended ischaemia time is 30 min for the liver and 60 min for the kidneys and lungs in adults; however, the corresponding data in cDCD are still inconclusive 6,8,15 . At present, there are no validated scales for the paediatric population to estimate the likelihood of death after WLST, 24 and there are few published studies on the variables that, in the case of the pediatric donor, predict death in a short time after WLST 25 . In this sense, the prospective study of the dying process in pediatric and neonates is needed, including these patients in studies similar to the one that has been recently published of the incidence and timing of resumption of cardiac electrical and pulsatile activity in adults who died after planned WLST 26 …”
Section: Discussionmentioning
confidence: 99%
“…6,8,15 At present, there are no validated scales for the paediatric population to estimate the likelihood of death after WLST, 24 and there are few published studies on the variables that, in the case of the pediatric donor, predict death in a short time after WLST. 25 In this sense, the prospective study of the dying process in pediatric and neonates is needed, including these patients in studies similar to the one that has been recently published of the incidence and timing of resumption of cardiac electrical and pulsatile activity in adults who died after planned WLST. 26 Second, pediatric donation, especially from neonates, is about family-centered care.…”
Section: Ta B L E 2 Characteristics Of the Infants Who Died After Eol Decisions At 38 Participating Hospitals During The Study Periodmentioning
confidence: 99%
“…For a patient to become a DCD donor, they must die within a specified amount of time depending on the country, institution, and protocol, with times ranging from 75 seconds up to as much as 20 minutes, although today most protocols in the United States utilize 2-5 minutes. 25,[38][39][40][41][42][43] Although tools to predict timing of death following the withdrawal of support exist, [44][45][46] knowledge of the mechanism of death may aid the pediatric provider in predicting time to death.…”
Section: Discussionmentioning
confidence: 99%